2022
DOI: 10.1002/hep4.1890
|View full text |Cite
|
Sign up to set email alerts
|

Features of Cirrhotic Cardiomyopathy Early in the Lives of Infants With Biliary Atresia Correlate With Outcomes Following Kasai Portoenterostomy

Abstract: Cirrhotic cardiomyopathy (CCM), detected during two‐dimensional echocardiography (2DE), is prevalent in patients with biliary atresia (BA) awaiting transplant. Whether CCM occurs early in the lives of infants with BA is unknown. The aim of this study was to explore the incidence and consequence of CCM in patients with BA, focusing on the earliest ages when 2DE was performed. A cohort of 78 patients with BA at a single center underwent 2DE (median age = 132 days) during the first year of life. Left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…A recent study shows that abnormalities in LV geometry are detected in early infancy and are associated with poor outcomes after Kasai porto-enterostomy (KPE). 12 Despite advances in the fields of cardiology and hepatology, the only current treatment option to reverse CCM is an LT. 4 The status quo in advancing care in this domain stems from a lack of understanding of the causative factors that lead to the development of CCM in BA. A deeper insight into metabolites that link liver dysfunction with structural and functional aberrations in the heart is needed to understand the pathogenesis of CCM if overall outcomes are to be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows that abnormalities in LV geometry are detected in early infancy and are associated with poor outcomes after Kasai porto-enterostomy (KPE). 12 Despite advances in the fields of cardiology and hepatology, the only current treatment option to reverse CCM is an LT. 4 The status quo in advancing care in this domain stems from a lack of understanding of the causative factors that lead to the development of CCM in BA. A deeper insight into metabolites that link liver dysfunction with structural and functional aberrations in the heart is needed to understand the pathogenesis of CCM if overall outcomes are to be optimized.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that elevated LVMI and RWT can predict poor outcomes after liver transplantation. And a recent study suggests that abnormal 2DE features are present early in life in patients with BA and usually occur at the age when BA is diagnosed ( 29 ). We surmise that if we compared these 2DE parameters to the whole pool of patients on a liver transplant waiting list, this extrahepatic feature could optimize organ allocation and direct clinical care in the future.…”
Section: Discussionmentioning
confidence: 99%
“…115 121 A recent study, interestingly, identified CCM early in the course of BA and found the ratio of LVMI to its upper limit of normal was a predictor of post-Kasai outcome. 125 Despite these differences in survival, studies found CCM is associated with higher ICU length of stay as well as multiorgan dysfunction, mechanical ventilation, and the need for pressor support prior to LT. 115 116 121 124 Adult guidelines recommend routine TTE at regular intervals before and after LT ( Table 2 ). 117 Approaches to surveillance for and monitoring of CCM in children are not well defined.…”
Section: Pathophysiology Diagnosis and Management Of Cirrhotic Cardio...mentioning
confidence: 99%